Methodological features of mobile applications for studying foreign languages created in Russia on the example of «Words – Учи иностранные языки» - Раднаев З. Б. - Ц. (2024, 2024)
This article conducts an analysis of methodological features of mobile applications for foreign language acquisition developed in Russia, specifically examining «Words – Учи иностранные языки», in comparison with the foreign applications «Quizlet» and «AnkiDroid». The study evaluates the functionality, pedagogical strengths, and limitations of each application, highlighting their unique features and particularities as tools for enhancing level of language knowledge